The association between fear of falling and functional tests in older adults with diabetes mellitus - Sakineh Jaddi Arani; Mahboubeh Rezaei; Mansour Dianati; Fatemeh Atoof (Nursing and Midwifery Studies, 2020)
Background: The number of older adults with diabetes mellitus (DM) is increasing. Falling during walking and the fear of it are prevalent in older adults with DM. Objective: This study aimed to examine the association between fear of falling (FoF) and functional tests in older adults with DM and to determine other factors affecting functional tests in these people. Methods: A cross-sectional study was conducted on 134 older adults with DM who had referred to the diabetes clinic of Matini Hospital in Kashan, Iran. The participants were selected through sequential sampling and then were categorized into two groups of “with” and “without FoF.” In addition to responding to a demographic questionnaire, the participants were assessed by the Mini-Mental State Examination, Diabetic Neuropathy Symptom Score, and Falls Efficacy Scale-International version. Walking performance of the participants was also measured using the Timed Up-and-Go, 5-Sit-to-Stand, and 50-Foot Timed Walk tests. Data were analyzed using the Chi-square, t-, and Mann–Whitney U-tests and linear regressions analysis. Results: Significant associations were found between FoF and education level, body mass index, waist-to-hip ratio, and having neuropathy (P < 0.05). In addition to FoF, a number of demographic, anthropometric, and clinical variables affected the patients' performance in all functional tests; however, gender was the variable that affected the results of all three tests (P < 0.05). Conclusion: FoF is associated with the performance of older adults with DM in functional tests. Thus, the FoF should be assessed in older adults with DM in order to provide better health care for them.